Risk Management Analysis on Infrastructure Construction Projects with Lumpsum System and Price Unit Contract System - Saeman Saeman; Nurly Gofar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to identify risks in various construction projects and what risk factors have the mostinfluence on each type of project at each stage, to find out which types of contracts have a high level of cost risk, higher time and quality between the two types of contracts based on the results of the analysis using the Analytic Hierarchy Process (AHP) method, analyzing risk on projects with lumpsum contracts and unit price, risk factors that influence these projects and which is more risky between the two contracts based on the results of the risk level analysis, conducting risk analysis on various construction projects based on the project owner and which is more risky between private or government project owners based on the results of the risk level analysis, developing a lump sum contract model and unit price whether m Indeed, there are different ways of handling risk for projects based on empirical data obtained from respondents. This implementation was carried out at the Jambi UIN STS Campus which is located at Jalan Jambi – Muara Bulian, Sungai Duren, Jambi Outer City District, Muaro Jambi Regency, Jambi 36657. This study uses Survey method using questionnaires and interviews (Interview). The data obtained were then processed and analyzed using the Analytical Hierarchy Process (AHP) method. Respondents in this study were contractors who had experience working on projects with lump sum contracts and unit price contracts. The number of respondents (sample) used is 32 respondents. The results of the analysis using the AHP method showed that in the construction project at the UIN STS Jambi Campus, the risk factor for the use of unit price contracts was higher than the lump sum contract with a ratio of 57.87%: 42.13%. From these results, it is recommended that contractors pay more attention to the dominant risk factors identified before participating in the tender process or before signing the contract as consideration for anticipating risks and avoiding project cost overruns, project completion time delays and the resulting project quality so as not to cause losses which is getting bigger.